Avery Brooks: capstone - Brooks, Avery, artist (Colorado State University. Libraries, 2026)
The artist's statement: I'm Avery Brooks Jr. I am a graphic designer from Fort Collins, Colorado. I primarily create photography, paintings, and digital designs. I have a Bachelor of Fine Arts in graphic design and will graduate this May. I have made many artworks that have been impactful to me. Subjects like photography, painting, and digital design have led me to become a better artist through challenging me to create abstract and landscape art to find my style as an artist. My inspirations are Saul Bass, Milton Glaser, and David Carson. The software I use for my graphic design process are Adobe products such as Illustrator, Premiere Pro, and Photoshop. I've also used physical mediums like photography to make landscape artwork that reflects reality in a very abstract and creative way. My work represents my deep want to explore the world and be inquisitive about others' ideas outside of my comfort zone. Art is a means of human connection that I want to touch upon more with different mediums. My mission in general is to be a better graphic designer and a stronger person. What pushes me to do this is to create better images for the corporate world and to improve its recent decline in terms of graphic design work. I believe in taking my time with my artwork so that I create quality results that reflect my creativity. I want to find something bigger than myself through my art and create my own authenticity. I hope to find inspiration from the artworks and to make novel art pieces that can make an impact on the world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design